2020
DOI: 10.1021/acsaem.0c00048
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of n-Type Zintl Phases RbAlSb4, RbGaSb4, CsAlSb4, and CsGaSb4

Abstract: Zintl phases are excellent candidates for high-efficiency thermoelectrics (TEs) due to their extremely low lattice thermal conductivity. The manufacturing of an all-Zintl module is particularly attractive for practical applications, as it alleviates concerns regarding the electronic, thermal, and mechanical compatibility of the p-and n-type legs. To date, a large majority of Zintl phases have been realized as p-type TE materials. Our recent discovery of n-type transport in Ba-doped KAlSb 4 and KGaSb 4 has help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 75 publications
4
25
0
Order By: Relevance
“…Figure 4(a) presents the summary of the computational search of new ABX 4 Zintl phases in the prototypical KGaSb 4 structure. Out of the 36 phases considered in this study, only 6 are known/reported, [11][12][13] indicating that the chemical phase space of ABX 4 compound is under-explored. From electronic structure calculations, we find that 25 out of 36 ABX 4 phases (in the assumed KGaSb 4 structure) have non-zero DFT band gap ( Figure 4a).…”
Section: Defect Energeticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 4(a) presents the summary of the computational search of new ABX 4 Zintl phases in the prototypical KGaSb 4 structure. Out of the 36 phases considered in this study, only 6 are known/reported, [11][12][13] indicating that the chemical phase space of ABX 4 compound is under-explored. From electronic structure calculations, we find that 25 out of 36 ABX 4 phases (in the assumed KGaSb 4 structure) have non-zero DFT band gap ( Figure 4a).…”
Section: Defect Energeticsmentioning
confidence: 99%
“…However, only a few n-type ones have been reported in experiments. [11][12][13][14] The inherent features of Zintl phases, such as small band gaps, dispersive electronic bands, and complex structures, make them suitable as TE materials. Zintl phases such as Yb 14 MnSb 11 , 15 in mid-to high-temperature regime.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations